Method for Evaluating the Effectiveness of Simulation Training for Laparoscopic Intracorporeal Suturing - A. V. Shabunin; A. V. Klimakov; Yu. I. Logvinov; R. Yu. Maer (Здоровье мегаполиса)
Laparoscopic intracorporeal suturing (LIS) is one of the key skills in laparoscopic surgery. LIS training is conducted in simulation centers and is aimed at transferring the knowledge into practice. The simulation training (ST) is focused on the development of skills that allow surgeons to perform LIS operations. However, this goal is not completely achieved: only 44,0 to 72,2 % of surgeons implement LIS skills in their practice. here is a need to evaluate the effectiveness of such training programs and analyze factors that may influence the results. This evaluation is required to increase the effectiveness of LIS trainings and implement the acquired skills into practice by training surgeons.According to commonly accepted approach to evaluation of training programs suggested by D. Kirkpatrick., the method of effectiveness evaluation allows to estimate the practical results achieved by all trainees. Unfortunately, there are no commonly accepted methods aimed at evaluating the effectiveness of LIS training programs. The existing methods estimate the results of effectiveness evaluation in simulation (Dry lab) or practically, but in small groups. Effectiveness evaluation of LIS trainings implementation in surgical practice among all trainees is related to significant financial costs and complexity.A new effectiveness evaluation method of LIS simulation training programs (the Method) has been suggested. It is aimed at evaluating the total amount of results and other ST effects, as well as analyzing individual factors that can influence training results. The Method includes a survey among ST participants. It has been applied to effectiveness evaluation of LIS simulation training program at Educational and Accreditation Center of the Botkin City Clinical Hospital. The survey showed that 88.9% of surgeons attending the LIS training program implemented their knowledge into practice.The suggested Method allows to evaluate the effectiveness of LIS simulation training and its implementation into practice among all trainees, analyze factors that can influence the training results and use the obtained results for further improvement of the training program and its methods. The Method may be recommended for implementation at medical simulation training centers.